2018
DOI: 10.1016/j.marpolbul.2017.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in bivalve larvae from the Puck Bay (Gulf of Gdansk, southern Baltic Sea) as an indicator of environmental pollution

Abstract: This study described the occurrence of abnormalities in bivalve larvae from the Puck Bay. Analyses of plankton samples collected in 2012-2013 showed that larval Mytilus trossulus, Mya arenaria, and Cerastoderma glaucum exhibited abnormalities that could indicate adverse environmental impacts. The deformities were mainly in shells, but missing soft tissue fragments and protruding vela were also noted. In addition to larval studies, we analyzed benthic postlarvae of Mytilus trossulus. Interestingly, grooves and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…High levels of heavy metals or toxic elements can also lead to malformation of organisms’ soft and hard tissue, as has been proven for a large number of living organisms ( Wang, Yang & Wang, 2009 ; Ma et al, 2011 ; Zhao et al, 2017 ; Lasota et al, 2018 ; Riani, Cordova & Arifin, 2018 ). For example, when copper (Cu) and zinc (Zn) were added to the water for feeding the foraminiferan Ammonia beccarii , the organisms developed abnormalities ( Sharifi, Croudace & Austin, 1991 ), and when scallops were placed in wastewater from a gold mine with concentrations of 14% and 50% for 6 h, the abnormality ratio increased by 6% and 21%, respectively ( Ma et al, 2011 ).…”
Section: Discussionmentioning
confidence: 96%
“…High levels of heavy metals or toxic elements can also lead to malformation of organisms’ soft and hard tissue, as has been proven for a large number of living organisms ( Wang, Yang & Wang, 2009 ; Ma et al, 2011 ; Zhao et al, 2017 ; Lasota et al, 2018 ; Riani, Cordova & Arifin, 2018 ). For example, when copper (Cu) and zinc (Zn) were added to the water for feeding the foraminiferan Ammonia beccarii , the organisms developed abnormalities ( Sharifi, Croudace & Austin, 1991 ), and when scallops were placed in wastewater from a gold mine with concentrations of 14% and 50% for 6 h, the abnormality ratio increased by 6% and 21%, respectively ( Ma et al, 2011 ).…”
Section: Discussionmentioning
confidence: 96%
“…Abnormalities in D-veligers were characterized based on observations by His et al [21], Saidov and Kosevich [22], and Lasota et al [23]. It is important to note that not all abnormally developing D-veligers had a singular abnormality and thus, during characterization, larvae were grouped based on the most prominent abnormality type.…”
Section: Scanning Electron Microscopy (Sem) Preserved D-veligersmentioning
confidence: 99%
“…Thus, knowledge gaps are remaining concerning these effects in marine ecosystems. Otherwise, the available data mainly focused on the effects of GBMs alone towards adult marine organisms (Khan et al 2019a, b;Li et al 2021), while in marine invertebrates, early life stages were shown to be more sensitive to pollutants (Lasota et al 2018). For this reason, there is a need to carefully evaluate their potential impact on marine species and interactions with other pollutants to properly regulate the use and disposal of GBMs, in order to prevent unexpected issues related to these nanomaterials (Hull 2019).…”
Section: Introductionmentioning
confidence: 99%